Quotes from Press Releases when Jane Tolmach filed for Assembly
This campaign statement from Jane Tolmach's 1976 Assembly run emphasizes her commitment to effective representation for Ventura County in Sacramento. She argues that the county deserves its fair share of state revenues for roads, transit, parks, mental health services, and education, and highlights the need for a four-year college in Ventura County to reduce costs and barriers for local students. Tolmach identifies tax reform as California's most urgent issue, supporting efforts to shift more responsibility to wealthy individuals and corporations while warning against increased reliance on regressive property taxes. She also pledges to be an independent, full-time legislator with no outside business interests, dedicating her time and energy solely to representing Ventura County residents.